Women's Political Participation and Intrahousehold Empowerment: Evidence from the Egyptian Arab Spring - Olivier Bargain; Delphine Boutin; Hugues Champeaux (Institute of Labor Economics (IZA), 2018)
Egyptian women have played an unprecedented role in the Arab Spring democratic movement, possibly changing women's perception about their own rights and role. We question whether these events have translated into better outcomes within Egyptian households. We conjecture that potential changes must have been heterogeneous and depended on the local intensity of protests and women's participation over 2011-13. We exploit the geographical heterogeneity along these two margins to conduct a double difference analysis using data surrounding the period. We find a significant improvement in women's final say regarding decisions on health, socialization and household expenditure, as well as a decline in the acceptation of domestic violence and girls' circumcision, in the regions most affected by the protests. This effect is not due to particular regional patterns or pre-existing trends in empowerment. It is also robust to alternative treatment definitions and confirmed by triple difference estimations. We confront our main interpretation to alternative mechanisms that could have explained this effect.
Keywords: J12; J16; D74; I14; 330; Arab Spring; revolutions; gender; empowerment; Egypt